2011
DOI: 10.1007/s00429-011-0320-2
|View full text |Cite
|
Sign up to set email alerts
|

Projections from the rat pedunculopontine and laterodorsal tegmental nuclei to the anterior thalamus and ventral tegmental area arise from largely separate populations of neurons

Abstract: Cholinergic and non-cholinergic neurons in the brainstem pedunculopontine (PPT) and laterodorsal tegmental (LDT) nuclei innervate diverse forebrain structures. The cholinergic neurons within these regions send heavy projections to thalamic nuclei and provide modulatory input as well to midbrain dopamine cells in the ventral tegmental area (VTA). Cholinergic PPT/LDT neurons are known to send collateralized projections to thalamic and non-thalamic targets, and previous studies have shown that many of the afferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 88 publications
3
43
0
Order By: Relevance
“…Currently, the mechanism by which M 4 activation regulates mesolimbic and mesostriatal dopaminergic transmission is unknown. M 4 has been postulated to act as an inhibitory autoreceptor on terminals of cholinergic neurons originating in the pedunculopontine and laterodorsal tegmental nuclei that excite dopaminergic neurons in the ventral tegmental area (Holmstrand and Sesack, 2011;Yeomans, 2012) and activation of M 4 autoreceptors in the VTA could reduce cholinergic excitation of dopamine neurons (Tzavara et al, 2004). In addition, activation of cholinergic interneurons in the NAS elicits dopamine release (Cachope et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the mechanism by which M 4 activation regulates mesolimbic and mesostriatal dopaminergic transmission is unknown. M 4 has been postulated to act as an inhibitory autoreceptor on terminals of cholinergic neurons originating in the pedunculopontine and laterodorsal tegmental nuclei that excite dopaminergic neurons in the ventral tegmental area (Holmstrand and Sesack, 2011;Yeomans, 2012) and activation of M 4 autoreceptors in the VTA could reduce cholinergic excitation of dopamine neurons (Tzavara et al, 2004). In addition, activation of cholinergic interneurons in the NAS elicits dopamine release (Cachope et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They provide only a minor cholinergic projection to the cerebral cortex, but may be responsible for substantial inputs to the hypothalamus and basal forebrain (Vincent et al, 1983b;Hallanger, 1988;Holmstrand and Sesack, 2011) and to the RVL (Ruggiero et al, 1990;Yasui et al, 1990). The largest outputs from the pedunculopontine and laterodorsal tegmental nuclei, however, are to the thalamus and to the medial pontine and medullary reticular formation (Edley and Graybiel, 1983;Hallanger et al, 1987;Rye et al, 1987;Hallanger, 1988;Krout et al, 2002;Rodrigo-Angulo et al, 2005;Holmstrand and Sesack, 2011). The latter projections have been implicated in initiating the switching process from slowwave to rapid eye movement (REM) sleep Datta and Siwek, 2002;Lu et al, 2006b), which is accompanied by an increase in sympathetic tone (Yasui et al, 1990;Trinder et al, 2001).…”
Section: Laterodorsal Tegmental Nucleus and Pedunculopontine Tegmentamentioning
confidence: 99%
“…The neurotransmitter or neuropeptide-like choline or orexin neurons found in the sleep-wake regulating nuclei (such as pedunculopontine tegmetal nucleus and lateral hypothalamus) [36] may project to the ventral tegmental area, one of the key rewarding systems in the brain, to relegate neural activity [37,38] . We found that sucrose preference (measured using a reward-based test for the interest in a sweet solution) [20] was correlated with sleep generation (light sleep bouts and total sleep time) and the REM sleep ratio, suggesting that the altered sleep time may reflect changes in the reward system.…”
Section: Wwwchinapharcom Wang Zj Et Almentioning
confidence: 99%